Measuring Social and Externality Benefits of in Influenza Vaccination - Corey White (Institute of Labor Economics (IZA), 2019)
Vaccination represents a canonical example of externalities in economics, yet there are few estimates of their magnitudes. I estimate social and externality benefits of influenza vaccination in two settings. First, using a natural experiment, I estimate the impacts of aggregate vaccination rates on mortality and work absences in the United States. Second, I examine a setting with large potential externality benefits: vaccination mandates for health care workers. I find that the social benefits of vaccination are substantial, most of benefits operate through an externality, and that the benefits of health care worker vaccination are particularly large.
Keywords: I12; I18; D62; H23; 330; vaccine; vaccination; influenza; flu; externality; health